2017
DOI: 10.1038/s41467-017-00304-1
|View full text |Cite|
|
Sign up to set email alerts
|

Non-coding RNAs participate in the regulatory network of CLDN4 via ceRNA mediated miRNA evasion

Abstract: Thousands of genes have been well demonstrated to play important roles in cancer progression. As genes do not function in isolation, they can be grouped into “networks” based on their interactions. In this study, we discover a network regulating Claudin-4 in gastric cancer. We observe that Claudin-4 is up-regulated in gastric cancer and is associated with poor prognosis. Claudin-4 reinforce proliferation, invasion, and EMT in AGS, HGC-27, and SGC-7901 cells, which could be reversed by miR-596 and miR-3620-3p. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
215
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(216 citation statements)
references
References 56 publications
1
215
0
Order By: Relevance
“…It is commonly known that EMT is important for cancer cell invasion and metastasis, including in GC cells . We detected the expression of EMT‐related proteins and found that SIX1 expression negatively correlated with E‐cadherin levels.…”
Section: Discussionmentioning
confidence: 93%
“…It is commonly known that EMT is important for cancer cell invasion and metastasis, including in GC cells . We detected the expression of EMT‐related proteins and found that SIX1 expression negatively correlated with E‐cadherin levels.…”
Section: Discussionmentioning
confidence: 93%
“…The procedure was carried out as previously described . Wt‐MALAT1 and mut‐MALAT1 as well as wt‐HDAC4 and mut‐HDAC4 were transcribed from vector pGEM ® ‐T (Promega) and biotin‐labeled with the Biotin RNA Labeling Mix (Roche, Basel, Switzerland) and T7 RNA polymerase (Roche), treated with RNase‐free DNase I (Roche), and purified with an RNeasy Mini Kit (Qiagen, Valencia, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The up‐regulation of miR‐29 could reduce lesion size and necrotic zones via targeting Col1A and Col3A . Recently, a novel regulatory mechanism among lncRNAs, miRNAs and their mRNA targets has been annotated in CVDs by pull‐down assay, chromatin immunoprecipitation (ChIP), luciferase reporter gene assay and quantitative reverse transcription polymerase chain reaction (qRT‐PCR) methods, although a plurality of evidence has revealed that lncRNA‐miRNA‐mRNA cascades participated in various pathophysiological processes in the field of oncology . In this review, four kinds of regulatory relationships were summarized: (a) the role of lncRNAs as miRNA sponges; (b) the coexpression of lncRNAs with miRNAs; (c) the reciprocal repression of lncRNAs and miRNAs; and (d) the role of miRNAs as negative regulators of lncRNAs.…”
Section: Introductionmentioning
confidence: 99%